The social environment and developmental experiences in elite youth soccer - Taylor, I. M.; Bruner, M. W. (Psychology of Sport and Exercise, 2012)
Objectives: We aimed to examine social-contextual correlates of players` developmental experiences in an elite youth soccer context. Specifically, we hypothesized that player perceptions of team cohesion and coach rapport would be positively associated with psychological need fulfillment. In turn, psychological need satisfaction was proposed to be positively related to adaptive developmental experiences in youth soccer (i.e., opportunities for leadership, emotional regulation, and goal setting), and negatively related to social exclusion. Design: Cross-sectional. Method: 133 male elite soccer players, aged between 11 and 18 years old, completed a self-report questionnaire assessing the variables of interest. Results: Using path analysis and bootstrapping methods, we found support for the overall model fit of the hypothesized conceptual framework and specific study hypotheses. Conclusions: This study utilizes strong theoretical foundations to underscore the role of the coach and team environment in facilitating positive youth outcomes, and highlights a potential mechanism that may explain these processes.